PENINGKATAN KEMAMPUAN KOGNITIF MELALUI MEDIA TANGRAM PADA ANAK KELOMPOK A DI BA ‘AISYIYAH KUNCEN CAWAS KLATEN - Melya Purbasari; Ihda A’yunil Khotimah (ABDAU : Jurnal Pendidikan Madrasah Ibtidaiyah, 2022)
This study aims to: 1) determine the application of tangram media to improve the cognitive abilities of group A children at BA 'Aisyiyah Kuncen Cawas Klaten, 2) to determine the improvement of cognitive abilities through tangram media to group A children at BA 'Aisyiyah Kuncen Cawas Klaten. The research method used in this study is the Classroom Action Research method, with data collection techniques in the form of observation, documentation, assignment techniques. The subjects in this study were group A students at BA 'Aisyiyah Kuncen Cawas Klaten, totaling 24 children consisting of 15 boys and 9 girls. The results of this study indicate that: 1) the application of tangram media to increase cognitive abilities in group A children in BA 'Aisyiyah Kuncen Cawas Klaten by a) introducing tangram media as a cognitive learning medium in group A, b) introducing the names of geometric shapes to tangram, c) move the tangram while counting it. 2) increasing cognitive abilities through tangram media in group A children at BA 'Aisyiyah Kuncen Cawas Klaten has increased. The score obtained in the pre cycle was 39.58%, cycle 1 was 59.37%, and cycle 2 was 86.45%. So the increase obtained is 46.87%. This means that there is a significant increase from the pre-cycle to cycle 2 results which show an increase in children's cognitive abilities.